PENERAPAN STRATEGI BELAJAR DISKUSI KELOMPOK KECIL/ BUUZGROUP UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR PENDIDIKAN DASAR OTOMOTIF MATA DIKLAT ALAT UKUR DI KELAS 10 TKR D SMK N 1 SEDAYU TAHUN 2014/2015 - Yudhi Kurniawan; Pairun Roniwijaya (Jurnal Taman Vokasi, 2015)
The purpose of this research was to know the learning process and automotive base education in measuring tool lesson achievement students of class 10 TKR D SMK N 1 Sedayu with small group discussion/Buzz group. This research is Classroom Action Research by using Kemmis model with two cycle of learning process. The subjects in this research were students of class 10 TKR D which is 24 students. The data collecting technique in this research was using observation and tests. The result of this research showed an increase in the learning process and achievement of students in the learning process. This is indicated by an increase in percentage of students learning process on the first cycle is 79% and on the second cycle increased to 79%. The percentage of the KKM students increased, first cycle at 66,66% increased to 91,66% in the second cycle.